A comprehensive review on the applications of nano-biosensor-based approaches for non-communicable and communicable disease detection. (14th April 2021) - George Kerry, Rout; Ukhurebor, Kingsley Eghonghon; Kumari, Swati; Maurya, Ganesh Kumar; Patra, Sushmita; Panigrahi, Bijayananda; Majhi, Sanatan; Rout, Jyoti Ranjan; Rodriguez-Torres, María del Pilar; Das, Gitishree; Shin, Han-Seung; Patra, Jayanta Kumar
Abstract : The outstretched application of biosensors in diverse domains has become the reason for its attraction to scientific communities. Abstract : The outstretched applications of biosensors in diverse domains has become the reason for their attraction for scientific communities. Because they are analytical devices, they can detect both quantitative and qualitative biological components through the generation of detectable signals. In the recent past, biosensors witnessed significant changes and developments in their design as well as features. Nanotechnology has revolutionized sensing phenomena by increasing biodiagnostic capacity in terms of specificity, size, and cost, resulting in exceptional sensitivity and flexibility. The steep increase of non-communicable diseases across the world has emerged as a matter of concern. In parallel, the abrupt outbreak of communicable diseases poses a serious threat to mankind. For decreasing the morbidity and mortality associated with various communicable and non-communicable diseases, early detection and subsequent treatment are indispensable. Detection of different biological markers generates quantifiable signals that can be electrochemical, mass-based, optical, thermal, or piezoelectric. Speculating on the incumbent applicability and versatility of nano-biosensors in large disciplines, this review highlights different types of biosensors along with their components and detection mechanisms. Moreover, it deals with the current advancements made in biosensors and the applications of nano-biosensors in detection of various non-communicable and communicable diseases, as well as future prospects of nano-biosensors for diagnostics.